Implementation of Academic Supervision for Human Resource Improvement at SMKN 1 Sungai Tabuk - Gilang Dwi Kurniawan; Resyadilla Azkia; Rida Maulidia; Marini Marini; Ahmad Suriansyah; Aslamiah Aslamiah (Journal of Educational Sciences, 2026)
The purpose of this study is to document best practices in the implementation of academic supervision by the principal to improve the quality of human resources (teachers) at SMKN 1 Sungai Tabuk. The research subjects consisted of 41 teachers. The research technique was carried out through pre-observation, observation (class visits by supervisors to observe the learning process) and post-observation, as well as collecting data from students about the learning process carried out by teachers. This study uses a qualitative approach, research data was collected through three main stages: pre-observation, observation, and post-observation and through triangulation of sources and techniques, namely by comparing the results of observations, interviews, and documentation to ensure the validity of the research findings. The results of the study indicate that academic supervision activities are able to improve various aspects of teacher weaknesses that have been obstacles to improving the quality of learning. Aspects such as discipline in carrying out teaching hours, orderly academic documents, awareness of educational innovation, implementation of Teaching Factory (TEFA) and Project Based Learning (PJBL), utilization of media and the internet, and utilization of information technology experienced significant improvements. Although not yet completely perfect, the results of supervision show positive changes towards increasing teacher professionalism at SMKN 1 Sungai Tabuk.